Validating the impact of gamified technology-enhanced learning environments on motivation and academic performance: enhancing TELEs with digital badges - Luo, Jiejin (Frontiers in Education, 2024)
This research focuses on validating the impact of gamified technology-enhanced learning environments (TELEs) on motivation and academic performance. The study aims to categorize and design digital badges based on game mechanics and to evaluate the effects of two distinct types of digital badges on learning outcomes. The research involved 95 university students learning classical Japanese grammar. The findings reveal that digital badges significantly enhance learners’ intrinsic motivation, positively affecting all five dimensions of intrinsic motivation, while their impact on extrinsic motivation was found to be minimal. Additionally, when comparing the two categories of digital badges, no significant differences in effectiveness were observed. The primary interest of this paper lies in exploring the design and efficacy of digital badges within technology-enhanced learning environments, contributing valuable insights into how these elements can enhance student engagement and learning outcomes.